2024
DOI: 10.1088/1742-6596/2687/8/082041
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade of the medium energy dump geometry for the SPIRAL2 single bunch selector

M Di Giacomo,
C Barthe-Dejean,
B Jacquot
et al.

Abstract: The medium energy beam transport of the SPIRAL2 superconducting linac contains a single bunch selection system equipped with a 7.5 kW beam dump. This device, originally designed with a long flat slope to decrease the power density so that the maximum operating temperature was 170 °C, was impacted by Coulomb scattering generating two side effects: heating of the downstream beam transport components and degrading of the beam current measurement uncertainty. The paper relates the way these two problems were solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the following run, it was found that the beam dump receiving the unused bunches deviated by the SBS (≤ 7.5 kW) was affected by Coulomb scattering producing an important heating degrading the beam current measurements. To reduce these effects, the beam dump was redesigned (surface changed from flat to staircase), constructed and installed, which successfully decreased the temperature and the current offset [25].…”
Section: Jinst 19 T05006mentioning
confidence: 99%
“…In the following run, it was found that the beam dump receiving the unused bunches deviated by the SBS (≤ 7.5 kW) was affected by Coulomb scattering producing an important heating degrading the beam current measurements. To reduce these effects, the beam dump was redesigned (surface changed from flat to staircase), constructed and installed, which successfully decreased the temperature and the current offset [25].…”
Section: Jinst 19 T05006mentioning
confidence: 99%